Experimental mixture designs as a tool for mango dairy cream optimization - Salamanca Grosso, Guillermo; Reyes Méndez, Laura M.; Osorio Tangarife, Mónica P.; Rodríguez Arias, Nelson (Revista Colombiana de Investigaciones Agroindustriales, 2015)
The design of mixtures for the development of new products, is one of the areas that has been gaining interest among food producers, given that you can do combinations of products looking for new functional characteristics and optimize the use of raw materials. This paper illustrates the design and optimization of dairy food using mango and yogurt, through sensory evaluation and experimental design of mixtures. We evaluated the necessary Sanitary and Hygienic conditions for the elaboration of new products and the implementation of a process for reduction of fruit particle size by sieving the pulp. There was a design of mixtures using mango, sugar cane as a sweetener and yogurt as a vehicle. We evaluated the physicochemical properties of the fruit at its optimal state of maturity and formulated mixtures for yogurt, fruit, valuing the effect of the components in the final formulations respect to acidity, pH, chromatically properties and sensory attributes. Best properties observed were with 15 g of sugar, 20 g of puree and 65 g of yogurt. Optimum pH were 3,97; total acidity of 98,8 meq kg-1 and soluble solids between 17,0 and 19,6 as maximum. The contribution lies in the valuation of the methodology of the designs for ternary mixtures that can be through sensory or physicochemical analysis. Para citar este artículo Salamanca, S., Reyes, L., Osorio, M. y Rodríguez, N. (2015). Diseño experimental de mezclas como herramienta para la optimización de cremolácteos de mango. Rev. Colomb. Investig. Agroindustriales, 2(1), 16-24. DOI: http://dx.doi.org/10.23850/24220582.166